[Rezension von: Australian jurists and Christianity] - Lucas, Brian (The Australasian Catholic record, 2022)
Review(s) of: Australian jurists + christianity, edited by Geoff Lindsay and Wayne Hudson, Alexandria, NSW: Federation, 2021, pp. 350, paperback, $99.00.